Coated Coated Wire, Coated Graphite and modified carbon paste Electrodes for Potentiometric Determination of Azithromycin: Coated wire coated graphite - K. Mohammed, Aveen; Saeed, Muthana; I. Haidar , Omed (ASJ - Academic Science Journal, 2024)
For the assessment of the drug azithromycin (AZ) in biological and pharmaceutical samples, three different types of ion selective electrodes were created: the modified carbon paste electrode (MCPE), coated graphite electrode (CGE), and coated wire electrode (CWE). The electrodes followed the Nernst equation in the range (1.0×10-7 - 1.0×10-1 , 1.0×10-6 - 1.0×10-1 and 1.0×10-5 - 1.0×10-1 )M range, with a slope of (58.355, 57.937, and 56,127) mV/decade and a low detection limit of (5.0339×10-8 , 5.111×10-7 and 4.8486×10-6 )M for (MCPE, CGE and CWE)electrodes respectively.The suggested sensors additionally demonstrated long-term stability and worked following preparation without significant changes in the potential or slope values, the analysis method is very sensitive and selective, and the t-test and F-test at a 95% confidence level were used to perform the statistics precisely and accurately.